Analisis Ujian Keahlian Pelaut (UKP) Berbasis Computer Based Asessment (CBA) Pada Politeknik Pelayaran Barombong - Syamsu; Rukmini; Miran; Satria, Yudi; Nenny; Made Alet, I; Ihsan, Fahri (Shofanah Media Berkah, 2024)
Learning outcomes are an indicator of educational quality; with technological advancements in the Computer Based Assessment (CBA)-based seafarer expertise test, it is hoped that CBA implementation can be carried out transparently. The objective of this study was to discover whether level IV training participants improved their readiness for the Barombong Maritime Polytechnic's Computer-Based Assessment (CBA), if done correctly and in accordance with what is tested by the Seafarer Expertise Examination Organizer. This study applied a survey method to describe the readiness of the examinees to take the computer-based assessment of seafarer skills exams. A total of 75 seafarer skills test participants were used in this study. In this study, the purposive sampling method was used. The study's findings indicated that the examinees were prepared to take the Seafarers Expertise Exam, as evidenced by a test score of 83.14% on the questionnaire for very good assessment, and that the organizers of the Seafarer Skills Exam were ready to conduct computer-based assessments without any obstacles. They must, however, continue to improve in order to achieve better results. The result of the study showed that: 1. Participants in the seafaring skill test have a high level of understanding (94.6%). 2. The respondent's business aspect is excellent (100%). 3. Aspects of respondents' ability in the very good category (100%). 4. The achievement value for the facility aspect is very high (98.7%).